THE ROLE OF TRANSFORMATIONAL LEADERSHIP STYLE IN DEVELOPING EMPLOYEE ENGAGEMENT AMONG GENERATION Y IN JAKARTA - Bambang Setiono, Christian Haposan Pangaribuan & Ayu Widya Meilani (International Journal of Research Science and Management, 2019)
Leaders as the driver of change have important presence in an organization to guide their followers and become more engaged with the organization. The level of engagement level of employees in Indonesia is quite low. Thus, leaders need to find the most effective way to improve this engagement level. The purpose of this study is to examine the influence of transformational leadership behaviors; idealized influence, intellectual stimulation, inspirational motivation and individual consideration, toward employee engagement of Generation Y in Jakarta, Indonesia. This study uses quantitative approach by using primary data and distributed questionnaires to 162 respondents. The data was analyzed through regression analysis. The result of this study shows that intellectual stimulation and inspirational motivation have a significant influence on employee engagement. Conversely, idealized influence and individual consideration show insignificant influence on employee engagement among Generation Y in Jakarta. Implications are provided to assist organizations to understand the importance of employee engagement